MARKET RISK CAPITAL CHARGE OF BONDS UNDER THE STANDARDIZED DURATION APPROACH: INSIGHTS FROM SBI - Verma , Nihal; Sinha , Avinash (Indian Journal of Finance and Banking, 2025)
This study examines the calculation of the market risk capital charge of bonds under the Standardized Duration Approach of the Basel norms. The background of the research lies in understanding how duration and modified duration determine a bond's sensitivity to interest rate movements and how these measures affect the computation of capital charges for market risk. The purpose of the study is to analyse the procedures involved in calculating market risk capital charges, validate the modified duration formula, and observe the changing patterns of capital charge requirements for the State Bank of India (SBI) over five years. The study uses SBI records and establishes a relationship between the 10-year government security yield and the capital charge for interest rate risk for the SBI group. A step-by-step methodological process of applying the Duration model is used to compute both the overall market risk and specific risk contributions. The results show a negative correlation of –0.21 between the 10-year government security yield and SBI's capital charge for interest rate risk. The analysis also indicates an overall increase in SBI's market risk capital charge over the five years, reflecting higher observed volatility. Significant findings include confirmation that understanding Duration and modified Duration is essential to measuring the sensitivity of bonds to interest rate fluctuations and that, as a bond's maturity increases, its modified Duration also increases, making longer-duration instruments more exposed to market fluctuations and resulting in higher capital charges.JEL Classification Codes: G21, G32, G12.